High-crystallinity nano cerium dioxide as well as preparation method and application thereof

Through the hydrothermal solvent-thermal synthesis method, the reaction rate and solvent composition are controlled to prepare high-crystalline nanoceria, which solves the problems of poor consistency, poor stability, low crystallinity and agglomeration of nanoceria in the prior art. , realizes efficient and stable preparation of nano ceria, and is suitable for use in the field of chemical mechanical polishing.

CN119390105APending Publication Date: 2025-02-07GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411522659.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

It is difficult to prepare nano ceria with uniform morphology, narrow size distribution and high crystallinity, and there are problems such as poor nucleation consistency, poor stability, low crystallinity and prone to agglomeration during the preparation process.

Method used

The hydrothermal solvent-thermal synthesis method is used to control the reaction rate of the cerium salt solution, use a mixed solvent formed by mixing organic solvents with water, and add polymers to prepare high-crystalline nanoceria without high-temperature calcination.

Benefits of technology

It has achieved the preparation of nano ceria powders with uniform particle size and high crystallinity, and solved the problems of poor nucleation consistency, poor stability, low crystallinity and agglomeration. It has stable process, large output and strong operability, which is suitable for scale Production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390105A_ABST
    Figure CN119390105A_ABST
Patent Text Reader

Abstract

The invention relates to high-crystallinity nano cerium dioxide as well as a preparation method and application thereof, and the preparation method comprises the following steps: adding cerium salt into a mixed solvent to obtain a cerium salt solution; the method comprises the following steps: mixing a cerium salt solution and a high-molecular polymer, carrying out heating reaction, and then carrying out solid-liquid separation, washing and drying to obtain high-crystallinity nano cerium dioxide, the high-crystallinity nano cerium dioxide is of a single-crystal structure; the average particle size of the high-crystallinity nano cerium dioxide is 50 nm to 400 nm. According to the preparation method of the high-crystallinity nano cerium dioxide, high-temperature calcination is not needed, the nano-scale cerium dioxide with a single-crystal structure is prepared by slowing down the reaction rate, based on the high-crystallinity cerium dioxide abrasive particles, through the prepared polishing solution, the material removal rate of polycrystalline silicon wafers is not lower than 100 nm / min, and the material removal rate of the polycrystalline silicon wafers is not lower than 100 nm / min. And meanwhile, the surface roughness of the wafer is not higher than 1.00 nm, and a good polishing effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical mechanical polishing, and in particular relates to high-crystallinity nano cerium dioxide and a preparation method and application thereof. Background Art

[0002] At present, the application of ceria polishing powder as abrasive in the chemical mechanical polishing and flattening process of integrated circuits has received close attention. In the chemical mechanical polishing process of the shallow trench isolation layer (STI) of the chip, ceria polishing powder / liquid has high removal efficiency and excellent selectivity for the silicon dioxide layer, while achieving a high flatness and reducing the defect formation of the silicon nitride layer. Compared with silicon oxide and aluminum oxide used as polishing abrasives in traditional processes, ceria polishing abrasives are not easy to deposit on the surface of the polished wafer, so that the wafer surface maintains good cleanliness, greatly reducing the difficulty of subsequent cleaning, and is a new abrasive that is very likely to replace silicon oxide and aluminum oxide. Researchers have shown through the study of ceria polishing performance that the morphology, structure, size and size distribution of ceria have an important influence on the polishing performance, which is one of the core indicators in chip polishing applications. The polishing of integrated circuits has extremely strict requirements on the polishing process and polishing effect. The parameters of different batches of polishing powder products are highly consistent and the polishing effect is stable. The surface roughness after polishing is required to be below 1nm and there are no scratches on the surface. Integrated circuit polishing has strict parameter requirements for cerium dioxide polishing powder, including uniform powder particle morphology, narrow particle size distribution, strict absence of large particles (control of D90 upper limit), and high powder crystallinity.

[0003] The commercially used cerium dioxide polishing powder is mainly obtained by thermal decomposition of cerium salts (such as cerium carbonate, cerium oxalate or cerium hydroxide) to obtain primary powders, and then mechanically grinded and graded to obtain the final product. However, the thermal decomposition method is difficult to control the morphology and size of the powder, and the powder particle size is large, mainly micron and submicron particles, and it is difficult to obtain nano-scale uniform morphology powder. The liquid phase synthesis method can easily prepare cerium dioxide with uniform morphology and narrow size distribution by controlling the nucleation and growth of particles.

[0004] However, there are still many problems with the cerium dioxide nanoparticles currently prepared based on hydrothermal, heat of solution, thermal decomposition, and sol-gel methods: 1) The direct precipitation reaction rate of cerium ions and alkali is too fast, making it difficult to control the nucleation and growth processes of cerium dioxide, resulting in poor consistency and stability of large-scale production products; 2) The prepared cerium dioxide particles are either small in size, with a particle size often less than 30nm, which is difficult to meet the requirements of efficient polishing; 3) Or the prepared powder particles have a relatively low crystallinity, and a high-temperature calcination process is required to improve the crystallinity of the particles. During the high-temperature calcination process, the particles are very likely to agglomerate and form large particles, making it difficult to ensure the acquisition of high-quality cerium dioxide powder.

[0005] Therefore, how to develop a high-crystallinity nano-cerium dioxide and its preparation method and use to obtain a uniform morphology, narrow size distribution, and high-crystallinity nano-cerium dioxide that meets the requirements of chemical mechanical polishing has become a problem that needs to be solved urgently. Summary of the invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a high-crystallinity nano-cerium dioxide and a preparation method and use thereof. The preparation method of the high-crystallinity nano-cerium dioxide of the present invention does not require high-temperature calcination, and nano-scale single-crystal structure cerium dioxide is prepared by slowing down the reaction rate. The prepared cerium dioxide has a uniform particle size distribution, controllable size and high crystallinity.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing high-crystallinity nano-cerium dioxide, the preparation method comprising:

[0009] Adding cerium salt to a mixed solvent to obtain a cerium salt solution; mixing the cerium salt solution with a high molecular polymer, heating for reaction, and then performing solid-liquid separation, washing, and drying to obtain high-crystallinity nano-cerium dioxide;

[0010] The mixed solvent includes water and an organic solvent;

[0011] The high-crystallinity nano-cerium dioxide is a single crystal structure;

[0012] The average particle size of the high crystallinity nano-cerium dioxide is 50-400nm, for example, it can be 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, 340nm, 360nm, 380nm or 400nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] The present invention uses long-chain alcohols or similar substances as solvents and reactants, which have low reactivity and can control the reaction rate, thereby realizing the controllable synthesis of high-crystallinity cerium dioxide nanocrystals. In the traditional method for preparing cerium dioxide nanomaterials, ethylene glycol or ethanol is generally used as a solvent to form a mixed solvent with water to prepare cerium dioxide nanopowders with uniform morphology. Its basic principle is to promote the precipitation of cerium salts to form cerium dioxide nanocrystals through the reaction of methanol, ethanol or ethylene glycol under high temperature conditions. However, due to the high reactivity of methanol, ethanol and ethylene glycol, the prepared cerium dioxide nanocrystals are often micron-nano particles formed by the accumulation of many small particles, and the crystallinity of the powder particles is low. High-temperature calcination is required to improve the crystallinity of the powder before polishing application, while the method of the present invention is simpler and more controllable.

[0014] The present invention adopts a hydrothermal solvent thermal synthesis method, uses a mixed solvent formed by mixing a single organic solvent with water, and controls the reaction speed by regulating the type of organic solvent and the reaction temperature, so as to achieve the purpose of controlling the nucleation and growth of cerium dioxide nanocrystals, and utilizes the slow growth of nanocrystals to achieve controllable synthesis of high-crystallinity nano cerium dioxide. The preparation method can prepare nano cerium dioxide powder with uniform particle size and high crystallinity without high-temperature calcination, and solves the problems of poor nucleation consistency, poor stability, low crystallinity and easy agglomeration of cerium dioxide in the prior art. In addition, the preparation method provided by the present invention has the characteristics of stable process, large output, strong operability and the like, and can be mass-produced.

[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0016] The volume ratio of the organic solvent to water in the mixed solvent is (0.05-1):1, for example, it can be 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably (0.1-1):1.

[0017] The present invention reduces the usage of organic solvents, is beneficial to subsequent wastewater treatment, and reduces production costs.

[0018] Preferably, the concentration of the cerium salt is 0.1mol / L-0.8mol / L, for example, it can be 0.1mol / L, 0.15mol / L, 0.2mol / L, 0.25mol / L, 0.3mol / L, 0.35mol / L, 0.4mol / L, 0.45mol / L, 0.5mol / L, 0.55mol / L, 0.6mol / L, 0.65mol / L, 0.7mol / L, 0.75mol / L or 0.8mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 0.3mol / L-0.6mol / L.

[0019] The present invention can regulate the reaction rate by controlling the concentration of the cerium salt within a suitable range, so that cerium dioxide can stably nucleate. If the concentration of the cerium salt is too high, the cerium dioxide grain size will be small, multiple morphologies will coexist, and the grain size distribution will be wide, and high-quality cerium dioxide nanocrystals cannot be obtained; if the concentration of the cerium salt is too low, the size of the prepared cerium dioxide grains will become large and the crystallinity will be low, which will directly affect the yield of the reaction.

[0020] Preferably, the organic solvent is an organic solvent miscible with water.

[0021] Preferably, the organic solvent includes any one of alcohols, ketones, pyrroles or furans.

[0022] Preferably, the alcohol includes any one of butanol, diethylene glycol, pentanol or glycerol.

[0023] Preferably, the ketones include acetone and / or butanone.

[0024] Preferably, the pyrroles include any one of pyrrole, pyrrole derivatives, N-methylpyrrole or N-methylpyrrole derivatives.

[0025] Preferably, the furans include tetrahydrofuran and / or tetrahydrofuran derivatives.

[0026] Preferably, the cerium salt comprises any one of cerous nitrate, ammonium cerous nitrate, cerous sulfate or cerous chloride, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of cerous nitrate and ammonium cerous nitrate, a combination of ammonium cerous nitrate and cerous sulfate, a combination of cerous sulfate and cerous chloride, a combination of cerous nitrate, cerous sulfate and cerous chloride, a combination of ammonium cerous nitrate, cerous sulfate and cerous chloride, a combination of cerous nitrate, ammonium cerous nitrate, cerous sulfate and cerous chloride, and a combination of cerous nitrate, ammonium cerous nitrate, cerous sulfate and cerous chloride, preferably cerous nitrate.

[0027] Preferably, the high molecular polymer includes any one of polyvinyl pyrrolidone, polyethylene glycol, hydroxypropyl cellulose or hydroxypropyl methylcellulose, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of polyvinyl pyrrolidone and polyethylene glycol, a combination of polyethylene glycol and hydroxypropyl cellulose, a combination of hydroxypropyl cellulose and hydroxypropyl methylcellulose, a combination of polyvinyl pyrrolidone, hydroxypropyl cellulose and hydroxypropyl methylcellulose, a combination of polyethylene glycol, hydroxypropyl cellulose and hydroxypropyl methylcellulose, and a combination of polyvinyl pyrrolidone, polyethylene glycol, hydroxypropyl cellulose and hydroxypropyl methylcellulose, preferably polyvinyl pyrrolidone.

[0028] Preferably, based on the total volume of the cerium salt solution, the amount of the high molecular polymer added is 1 g / L-100 g / L, for example, it can be 1 g / L, 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L or 100 g / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the heating temperature is 120°C-220°C, for example, it can be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the heating time is 2h-30h, for example, 2h, 6h, 10h, 15h, 20h, 25h or 30h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the drying temperature is 80°C-110°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the drying time is 2 h-30 h, for example, 2 h, 6 h, 10 h, 15 h, 20 h, 25 h or 30 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In a second aspect, the present invention provides a high-crystallinity nano-cerium dioxide prepared by the method for preparing high-crystallinity nano-cerium dioxide as described in the first aspect.

[0034] The high-crystallinity nano-cerium dioxide provided by the invention has an octahedral morphology, and the powder particles have high crystallinity, uniform morphology, narrow particle size distribution, and no large particles exist.

[0035] Preferably, the high crystallinity nano cerium dioxide is a single crystal structure, and the average particle size of the high crystallinity nano cerium dioxide is 50nm-400nm, for example, it can be 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, 340nm, 360nm, 380nm or 400nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In a third aspect, the present invention provides a use of the high-crystallinity nano-cerium dioxide as described in the second aspect, wherein the high-crystallinity nano-cerium dioxide is used for chemical mechanical polishing.

[0037] The high-crystallinity nano-cerium dioxide provided by the present invention is used in the field of chemical mechanical polishing. The prepared abrasive particles have uniform morphology, narrow particle size distribution, good dispersibility, high stability after dispersion, and stable polishing effect. After polishing, the surface roughness of the polished part is below 1nm and there are no scratches on the surface.

[0038] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0039] Compared with the prior art, the present invention has at least the following beneficial effects:

[0040] (1) The present invention adopts a hydrothermal solvent thermal synthesis method, using a mixed solvent formed by mixing a single organic solvent with water, and controls the nucleation and growth of cerium dioxide nanocrystals to prepare high-crystallinity nano-cerium dioxide. The preparation method can prepare nano-cerium dioxide powder with uniform particle size and high crystallinity without high-temperature calcination, which solves the problems of poor nucleation consistency, poor stability, low crystallinity and easy agglomeration of cerium dioxide in the prior art. In addition, the preparation method provided by the present invention has the characteristics of stable process, large output, strong operability, etc., and can be mass-produced.

[0041] (2) The high-crystallinity nano-cerium dioxide provided by the present invention has an octahedral morphology, a uniform powder particle morphology, a narrow particle size distribution, no large particles, and a high degree of crystallinity.

[0042] (3) The high-crystallinity nano-cerium dioxide provided by the present invention is used in the field of chemical mechanical polishing. The prepared abrasive can maintain a high degree of consistency and a stable polishing effect. After polishing, the surface roughness of the polished part is less than 1 nm and there are no scratches on the surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a scanning electron microscopic analysis image of the high-crystallinity nano-cerium dioxide obtained in Example 1 of the present invention;

[0044] Figure 2 The X-ray diffraction pattern of the powder of high-crystallinity nano-cerium dioxide obtained in Example 1 of the present invention;

[0045] Figure 3 This is a laser particle size analysis diagram of the dispersion of high-crystallinity nano-cerium dioxide obtained in Example 1 of the present invention;

[0046] Figure 4 The high-resolution transmission electron microscopic analysis and single-particle electron diffraction analysis diagram of the high-crystallinity nano-cerium dioxide obtained in Example 1 of the present invention;

[0047] Figure 5 This is a scanning electron microscopic analysis image of the high-crystallinity nano-cerium dioxide obtained in Example 2 of the present invention;

[0048] Figure 6 This is a scanning electron microscopic analysis image of the high-crystallinity nano-cerium dioxide obtained in Example 3 of the present invention;

[0049] Figure 7 This is a scanning electron microscopic analysis image of the cerium dioxide powder obtained in Example 4 of the present invention;

[0050] Figure 8 This is a scanning electron microscopic analysis image of the cerium dioxide powder obtained in Example 5 of the present invention;

[0051] Fig. 9 This is a scanning electron microscopic analysis image of the cerium dioxide powder obtained in Example 6 of the present invention;

[0052] Fig.10 This is a scanning electron microscopic analysis image of the cerium dioxide powder obtained in Example 7 of the present invention;

[0053] Fig.11 This is a scanning electron microscopic analysis image of the cerium dioxide powder obtained in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0055] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.

[0056] Example 1

[0057] This embodiment provides a method for preparing high-crystallinity nano-cerium dioxide, the preparation method comprising the following steps:

[0058] Cerous nitrate hexahydrate (analytical grade) was added to a mixed solvent of butanol: water in a volume ratio of 0.6:1 to obtain a cerium salt solution with a concentration of 0.3 mol / L; the cerium salt solution was mixed with a polyvinyl pyrrolidone (K30) polymer based on the total volume of the cerium salt solution to obtain a reaction solution with a volume concentration of 50 g / L of the polyvinyl pyrrolidone (K30) polymer, and the reaction solution was heated at 180° C. for 12 h, and then solid-liquid separation, washing, and drying at 80° C. for 12 h were performed to obtain high-crystallinity nano-cerium dioxide;

[0059] The high-crystallinity nano-cerium dioxide is a single crystal structure;

[0060] The average particle size of the high-crystallinity nano-cerium dioxide is 76 nm.

[0061] Figure 1 This is a scanning electron microscope (SEM) photo of high-crystallinity nano-cerium dioxide. The picture results show that the powder is composed of octahedral particles with distinct corners and edges, and presents monodisperse characteristics and uniform particle size distribution, with an average size of 76nm. After the nano-cerium dioxide powder is dispersed to obtain a cerium dioxide dispersion, the laser particle size analysis results show that the D50 of the particles in the solution is 82nm, and the particle distribution is narrow, showing a monodisperse state. The size of the scanning electron microscope photo is slightly smaller than the size of the dynamic light scattering particle size analysis result, but the uniform distribution of the particles is consistent.

[0062] Figure 2 The X-ray diffraction analysis (XRD) spectrum of high-crystallinity nano-cerium dioxide shows that the prepared powder is pure cerium dioxide (cubic fluorite structure). The secondary diffraction of the (111) crystal plane, (200) crystal plane, (220) crystal plane, (311) crystal plane, and (111) crystal plane of cerium dioxide can be clearly presented in the spectrum, and the peak shape is sharp, indicating that the prepared cerium dioxide has good crystallinity. According to the Scherrer formula, the CeO2 grain size is greater than 50nm, which is basically consistent with the size of a single cerium dioxide particle, indicating that the octahedral cerium dioxide is a single crystal particle with good crystallinity.

[0063] Figure 3This is a laser particle size analysis diagram of a dispersion of high-crystallinity nano-cerium dioxide. It can be seen that the distribution of CeO2 particles is narrow and the grain size is very uniform.

[0064] Figure 4 It is a transmission electron microscope (TEM) photograph of high-crystallinity nano-cerium dioxide and an electron diffraction pattern of a single particle. The hexagonal symmetric diffraction pattern shows that the octahedral cerium dioxide nanocrystals are single-crystal nanoparticles with good crystallinity.

[0065] Example 2

[0066] This embodiment provides a method for preparing high-crystallinity nano-cerium dioxide, the preparation method comprising the following steps:

[0067] Adding ammonium cerium nitrate hexahydrate (analytical grade) to a mixed solvent of diethylene glycol: water in a volume ratio of 0.2:1 to obtain a cerium salt solution with a concentration of 0.1 mol / L; mixing the cerium salt solution with a polyethylene glycol polymer based on the total volume of the cerium salt solution to obtain a reaction solution with a volume concentration of the polyethylene glycol polymer of 1 g / L, heating the reaction solution at 220°C for 2 hours, and then subjecting the reaction solution to solid-liquid separation, washing, and drying at 80°C for 18 hours to obtain high-crystallinity nano-cerium dioxide;

[0068] like Figure 5 As shown, the average particle size of the high-crystallinity nano-cerium dioxide is 53 nm, the particle morphology is uniform, and the size distribution is narrow.

[0069] Example 3

[0070] This embodiment provides a method for preparing high-crystallinity nano-cerium dioxide, the preparation method comprising the following steps:

[0071] Cerious nitrate hexahydrate (analytical grade) is added to a mixed solvent of tetrahydrofuran: water in a volume ratio of 1:1 to obtain a cerium salt solution with a concentration of 0.8 mol / L; the cerium salt solution is mixed with a hydroxypropyl cellulose polymer based on the total volume of the cerium salt solution to obtain a reaction solution with a volume concentration of 100 g / L of the hydroxypropyl cellulose polymer, the reaction solution is heated at 140°C for 30 hours, and then subjected to solid-liquid separation, washing, and drying at 80°C for 10 hours to obtain high-crystallinity nano-cerium dioxide.

[0072] like Figure 6 As shown, the average particle size of the high-crystallinity nano-cerium dioxide is 96 nm.

[0073] Example 4

[0074] This embodiment provides a method for preparing high-crystallinity nano-cerium dioxide, which differs from embodiment 1 only in that the volume ratio of butanol to water in the mixed solvent is 0.01: 1. The amount of product obtained after the reaction in this embodiment is relatively small, because most of the cerium salt is not completely reacted and still exists in the solution in the form of ions.

[0075] The crystalline nano cerium dioxide (such as Figure 7 The cerium dioxide nanoparticles (as shown) are composed of nanometer cerium dioxide particles of various sizes. The distribution range of the cerium dioxide particles is severely widened, ranging from 300nm to 500nm, and the average particle size is 360nm.

[0076] Example 5

[0077] This embodiment provides a method for preparing high-crystallinity nano-cerium dioxide, which is different from Embodiment 1 only in that the volume ratio of butanol:water in the mixed solvent is 3:1.

[0078] like Figure 8 As shown, the crystalline nano-cerium dioxide is a polycrystalline nano-cerium dioxide particle composed of small particles, the particle crystallinity is reduced, and the average particle size of the cerium dioxide particles is 90nm.

[0079] Example 6

[0080] This embodiment provides a method for preparing high-crystallinity nano-cerium dioxide, which is different from Example 1 only in that cerous nitrate hexahydrate (analytical grade) is added to a mixed solvent with a volume ratio of butanol: water of 0.6:1 to obtain a cerium salt solution with a concentration of 0.08 mol / L, and the other steps remain unchanged.

[0081] like Fig. 9 As shown, the average particle size of the high-crystallinity nano-cerium dioxide is 400 nm, and the particle size distribution is uniform, but the cerium salt concentration is low and the yield of cerium dioxide powder is low.

[0082] Example 7

[0083] This embodiment provides a method for preparing high-crystallinity nano-cerium dioxide, which is different from Example 1 only in that cerous nitrate hexahydrate (analytical grade) is added to a mixed solvent with a volume ratio of butanol: water of 0.6:1 to obtain a cerium salt solution with a concentration of 1.0 mol / L, and the other steps remain unchanged.

[0084] like Fig.10 As shown, the powder is mostly composed of octahedral particles (105nm), with a small amount of porous loose spheres (500nm). The octahedron is a hollow structure, the sphere size is large, a variety of morphologies coexist, and the size distribution is wide. Compared with Example 1, the cerium dioxide particles prepared in this example are composed of small particles, and the crystallinity is reduced.

[0085] Example 8

[0086] This embodiment provides a method for preparing high-crystallinity nano-cerium dioxide, which is different from Embodiment 1 only in that the composition of the mixed solvent is butanol:ethylene glycol:water in a volume ratio of 0.3:0.3:1, and the other steps remain unchanged.

[0087] The average particle size of the crystalline nano-cerium dioxide is 65 nm. Compared with Example 1, the crystallinity of the cerium dioxide particles prepared in this example is lower.

[0088] Comparative Example 1

[0089] This comparative example provides a method for preparing nano-cerium dioxide, which is different from Example 1 only in that the obtained high-crystallinity nano-cerium dioxide is heated to 500°C and calcined for 1 hour, then naturally cooled to room temperature, and fully ground to obtain nearly spherical cerium oxide abrasive particles; after calcination, the size of the cerium dioxide particles remains unchanged at about 76nm, but a considerable part of the particles agglomerate, and two particles and multiple particles agglomerate together to form sintered agglomerates larger than micron size, and the agglomerated particles remain agglomerated after long-term ultrasonic dispersion.

[0090] Comparative Example 2

[0091] This comparative example provides a method for preparing nano-cerium dioxide, which differs from Example 1 only in that polyvinyl pyrrolidone (K30) polymer is not added, and the other steps remain unchanged;

[0092] The cerium dioxide powder prepared in this comparative example consists of spherical particles and agglomerated block solids. The sizes of the spherical particles range from hundreds of nanometers to several micrometers, while the agglomerated block solids are particles above micrometer level.

[0093] Comparative Example 3

[0094] This comparative example provides a method for preparing nano-cerium dioxide, which is different from Example 1 only in that butanol is replaced by an equal amount of ethanol, and the other steps remain unchanged.

[0095] like Fig.11 As shown, the cerium dioxide powder prepared in this comparative example is a nearly spherical particle, the average size of the spherical particle is 58nm, the particle surface is rough, and it is composed of small-sized particles, presenting a polycrystalline state, and the particle crystallinity is low. This is because the ethanol reaction activity is high, the nucleation and growth rate are fast, resulting in a small particle size and growth into polycrystalline nanoparticles.

[0096] Application Examples

[0097] The cerium dioxide prepared in the above Examples 1-8 and Comparative Examples 1-3 was respectively prepared into polishing liquids by the following steps:

[0098] (1) Dissolve hexadecyltrimethylammonium bromide (CTAB) in 800 mL of deionized water to a CTAB concentration of 0.5 wt %; add 16 g of the cerium dioxide prepared in the above embodiment or comparative example, and disperse by ultrasonic for 10 min to form a cerium dioxide suspension with a concentration of 2 wt %;

[0099] (2) adding KMnO4 to the cerium dioxide suspension under magnetic stirring to make the concentration of KMnO4 0.05 mol / L;

[0100] (3) The pH value of the system was adjusted to 9 with potassium hydroxide solution, and magnetic stirring was continued for 10 minutes to obtain a cerium dioxide polishing solution.

[0101] The polishing liquid prepared by the above method was subjected to polishing test:

[0102] The chemical mechanical polishing test was performed on the oxidized polysilicon wafers using a polishing machine (Shenyang Kejing UNIPOL-1200S). The surface roughness of the polysilicon wafers before polishing was above 10nm, the polishing pad was IC-1000, the polishing pressure was 3psi, the upper / lower plate speed was 80 / 120rpm, the polishing liquid flow rate was 100ml / min, and after polishing for 5min, it was continued to be polished with deionized water for 1min to remove the particles that may remain on the polished surface. Each group of tests was repeated 3 times.

[0103] Table 1

[0104] Average particle size / nm <![CDATA[Polishing rate / nm·min -1 > Roughness / nm Example 1 76 118.6 0.33 Example 2 53 102.7 0.28 Example 3 96 164.2 0.38 Example 4 360 244.2 0.96 Example 5 90 28.7 0.80 Example 6 400 263.2 0.98 Example 7 105 31.3 0.67 Example 8 65 42.8 0.70 Comparative Example 1 76 215.4 1.28 Comparative Example 2 1000 334.5 1.36 Comparative Example 3 58 16.5 0.76

[0105] The test results show that:

[0106] (1) It can be seen from Examples 1-3 that the present invention adopts a hydrothermal solvent thermal synthesis method to prepare high-crystallinity nano-cerium dioxide by slowing down the reaction rate, and obtains high-crystallinity nano-cerium dioxide with uniform particle morphology, narrow particle size distribution, no large particles and high crystallinity. The prepared abrasive can maintain a high degree of consistency and a stable polishing effect. The polishing speed can reach about 100 nm / min. The surface roughness after polishing is below 0.40 nm, the surface is free of scratches, and the effect is excellent.

[0107] (2) By comparing Example 1 with Examples 4-5, it can be seen that the present invention further controls the volume ratio of organic solvent to water, reduces the amount of organic solvent used, is beneficial to subsequent wastewater treatment, reduces production costs, and regulates the reaction rate so that cerium dioxide can stably nucleate. At the same time, the cerium dioxide grain size is controlled to be below 100nm, which is beneficial to ensure that a higher polishing speed is obtained under the premise of a lower roughness (less than 0.40nm). When the particle size increases, although it has a higher polishing speed, the roughness after polishing also increases significantly, which is not conducive to chip polishing applications. The particle crystallinity decreases, the polishing speed decreases, and the roughness does not achieve the expected effect under the same polishing time.

[0108] (3) By comparing Example 1 with Examples 6-7, it can be seen that the present invention can regulate the reaction rate by further controlling the concentration of the cerium salt within an appropriate range, so that cerium dioxide can stably nucleate. If the concentration of the cerium salt is too high, the cerium dioxide grain size will be smaller, multiple morphologies will coexist, and the size distribution will be wider, and high-quality cerium dioxide nanocrystals cannot be obtained. If the concentration of the cerium salt is too low, the cerium dioxide grain size will be larger and the reaction yield will be directly affected.

[0109] (4) It can be seen from Example 1 and Comparative Example 1 that if high-temperature sintering is performed after the synthesis of cerium dioxide, it is not only easy for the nano-scale cerium dioxide particles to agglomerate into large particles, but also easy to cause serious scratches when used as a polishing liquid, thereby increasing the roughness of the surface after polishing. However, the present invention can prepare nano-cerium dioxide powder with uniform particle size and high crystallinity without high-temperature calcination.

[0110] (5) It can be seen from Example 1 and Comparative Example 2 that, in the absence of a polymer protective agent, cerium dioxide particles tend to agglomerate and grow into large particles. However, in the present invention, by adding a polymer, the process of grain nucleation and growth can be regulated, so that cerium dioxide can nucleate and grow uniformly.

[0111] (6) It can be seen from Example 1 and Comparative Example 3 that if ethanol is used as a solvent to form a mixed solvent with water to prepare cerium dioxide nanopowder, due to the high reaction activity of ethanol, the prepared cerium dioxide nanocrystals are often micron-nano particles formed by the accumulation of numerous small particles, the crystallinity of the powder particles is low, and the polishing effect is poor.

[0112] In summary, the present invention adopts a hydrothermal solvent thermal synthesis method, uses a mixed solvent formed by mixing a single organic solvent with water, and adds a high molecular polymer for adjustment. Nano cerium dioxide powder with uniform particle size and high crystallinity can be prepared without high-temperature calcination. The powder particles have uniform morphology, narrow particle size distribution, no large particles and high crystallinity. It is used in the field of chemical mechanical polishing. The prepared abrasive can maintain a high degree of consistency and a stable polishing effect. The surface roughness after polishing is less than 1 nm, and there are no scratches on the surface.

[0113] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing high-crystallinity nano-cerium dioxide, characterized in that: The preparation method comprises: Adding cerium salt to a mixed solvent to obtain a cerium salt solution; mixing the cerium salt solution with a high molecular polymer, heating for reaction, and then performing solid-liquid separation, washing, and drying to obtain high-crystallinity nano-cerium dioxide; The mixed solvent includes water and an organic solvent; The high-crystallinity nano-cerium dioxide is a single crystal structure; The average particle size of the high-crystallinity nano-cerium dioxide is 50nm-400nm.

2. The preparation method according to claim 1, characterized in that: The volume ratio of the organic solvent to water in the mixed solvent is (0.05-1):1; Preferably, the concentration of the cerium salt is 0.1 mol / L-0.8 mol / L, preferably 0.3 mol / L-0.6 mol / L.

3. The preparation method according to claim 1 or 2, characterized in that: The organic solvent is a water-soluble organic solvent; Preferably, the organic solvent includes any one of alcohols, ketones, pyrroles or furans; Preferably, the alcohol includes any one of butanol, diethylene glycol, pentanol or glycerol; Preferably, the ketones include acetone and / or butanone; Preferably, the pyrroles include any one of pyrrole, pyrrole derivatives, N-methylpyrrole or N-methylpyrrole derivatives; Preferably, the furans include tetrahydrofuran and / or tetrahydrofuran derivatives; Preferably, the cerium salt includes any one of cerous nitrate, ammonium cerous nitrate, cerous sulfate or cerous chloride, or a combination of at least two thereof.

4. The preparation method according to any one of claims 1 to 3, characterized in that The high molecular polymer includes any one of polyvinyl pyrrolidone, polyethylene glycol, hydroxypropyl cellulose or hydroxypropyl methyl cellulose, or a combination of at least two thereof.

5. The preparation method according to any one of claims 1 to 4, characterized in that: Based on the total volume of the cerium salt solution, the added amount of the high molecular polymer is 1 g / L-100 g / L.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The heating temperature is 120°C-220°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The heating time is 2h-30h.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The drying temperature is 80°C-110°C; Preferably, the drying time is 2h-30h.

9. A high crystallinity nano cerium dioxide, characterized in that: The high-crystallinity nano-cerium dioxide is prepared by the preparation method according to any one of claims 1 to 8; The high-crystallinity nano-cerium dioxide has a single crystal structure, and the average particle size of the high-crystallinity nano-cerium dioxide is 50nm-400nm.

10. A use of the high crystallinity nano-cerium dioxide as claimed in claim 9, characterized in that: The high-crystallinity nano-cerium dioxide is used for chemical mechanical polishing.

Citation Information

Cited By

  • Gadolinia-doped ceria nanomaterial, preparation method and application thereof

    CN122853435A